Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1152/ajprenal.0009.2001
|View full text |Cite
|
Sign up to set email alerts
|

A role for Wnt-4 in renal fibrosis

Abstract: Wnt-4 is a secreted glycoprotein that is critical for genitourinary development but found only in the most distal collecting duct epithelium in the normal murine adult kidney. Wnt4 expression is induced throughout the collecting ducts in four murine models of renal injury that produce tubulointerstitial fibrosis: folic acid-induced nephropathy, unilateral ureteral obstruction, renal needle puncture, and genetic polycystic kidney disease. Wnt4 activation induced by injury is limited to collecting ducts, with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
137
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(148 citation statements)
references
References 47 publications
7
137
1
2
Order By: Relevance
“…Recent evidence has identified ␤-catenin, a powerful regulator of cell proliferation, as a key effector in fibrosis of both pulmonary and extrapulmonary organs. 41 Chilosi et al 18 reported evidence of aberrant Wnt/ ␤-catenin activation in fibroproliferative bronchiolar lesions and also nuclear ␤-catenin accumulation in the fibroblastic foci in lung samples from patients with IPF. More recently, Konigshoff et al 30 reported that WISP1, a target gene of the Wnt/␤-catenin pathway, is a key regulator of pulmonary fibrosis through its ability to induce collagen matrix deposition by fibroblasts and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has identified ␤-catenin, a powerful regulator of cell proliferation, as a key effector in fibrosis of both pulmonary and extrapulmonary organs. 41 Chilosi et al 18 reported evidence of aberrant Wnt/ ␤-catenin activation in fibroproliferative bronchiolar lesions and also nuclear ␤-catenin accumulation in the fibroblastic foci in lung samples from patients with IPF. More recently, Konigshoff et al 30 reported that WISP1, a target gene of the Wnt/␤-catenin pathway, is a key regulator of pulmonary fibrosis through its ability to induce collagen matrix deposition by fibroblasts and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Surendran et al (34) recently observed low levels of Wnt-4 mRNA in the normal adult mouse kidney and that high levels of Wnt-4 expression induced in the collecting ducts in murine models of renal injury that produced tubulointerstitial fibrosis. In the ischemia/reperfusion model in our study, we did not observe a fibrotic area in the proximal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…The folic acid (FA)-induced renal injury model has been applied recently for evaluation of epithelial regeneration and interstitial fibrosis. [21][22][23][24] Intraperitoneal administration of FA with sodium bicarbonate induced renal injury that showed acute tubular necrosis with transient elevations of blood urea nitrogen (BUN) and serum creatinine (Cr) followed by development of interstitial fibrosis with macrophage infiltration. 21,25 Tubular obstructions by FA crystals and direct toxic effect of FA to tubular epithelial cells presumably cause renal damage, 26 but the precise mechanism of injury remains unclear.…”
mentioning
confidence: 99%